Gemifloxacin, a Fluoroquinolone Antimicrobial Drug, Inhibits Migration and Invasion of Human Colon Cancer Cells. (10th December 2013) - Kan, Jung-Yu; Hsu, Ya-Ling; Chen, Yen-Hsu; Chen, Tun-Chieh; Wang, Jaw-Yuan; Kuo, Po-Lin
Abstract : Gemifloxacin (GMF) is an orally administered broad-spectrum fluoroquinolone antimicrobial agent used to treat acute bacterial exacerbation of pneumonia and bronchitis. Although fluoroquinolone antibiotics have also been found to have anti-inflammatory and anticancer effects, studies on the effect of GMF on treating colon cancer have been relatively rare. To the best of our knowledge, this is the first report to describe the antimetastasis activities of GMF in colon cancer and the possible mechanisms involved. Results have shown that GMF inhibits the migration and invasion of colon cancer SW620 and LoVo cells and causes epithelial mesenchymal transition (EMT). In addition, GMF suppresses the activation of NF- κ B and cell migration and invasion induced by TNF- α and inhibits the TAK1/TAB2 interaction, resulting in decreased I κ B phosphorylation and NF- κ B nuclear translocation in SW620 cells. Furthermore, Snail, a critical transcriptional factor of EMT, was downregulated after GMF treatment. Overexpression of Snail by cDNA transfection significantly decreases the inhibitory effect of GMF on EMT and cell migration and invasion. In conclusion, GMF may be a novel anticancer agent for the treatment of metastasis in colon cancer.